Potential of Cover Crop Use and Termination with a Roller-Crimper in a Strip-Till Silage Maize (Zea mays L.) Production System in the Central Valley of California - Robert Willmott; Jennifer Valdez-Herrera; Jeffrey P. Mitchell; Anil Shrestha (Agronomy)
The potential of terminating cover crops with a roller-crimper is of increasing interest. A two-year (2020/21 and 2021/22) study was conducted in Fresno, CA, USA. Five cover crop treatments (rye (Secale cereale L.) alone, ultra-high diversity mix, multiplex cover crop mix, fava bean (Vicia faba L.) + phacelia (Phacelia tanacetifolia Benth.), and rye + field pea (Pisum sativum L.) + purple vetch (Vicia americana Muhl. Ex Willd.)) were planted in November, roller-crimped in April, and silage maize (Zea mays L.) was strip-till planted in the residue in May. Cover crop kill, soil cover by residue, weed cover, amount of organic residue, and silage maize yield were recorded. The roller-crimper resulted in 95 to 100% kill of the cover crops. Soil cover at maize canopy closure (mid-July) was approximately 90% in the rye plots while it was 30 to 70% in the other treatments. The fava bean + phacelia cover crop disintegrated the most rapidly. Weed cover was <5% in all the treatments until maize canopy closure. The cover crops added 6.7 to 14 MT ha−1 of residue. Maize silage yield was similar across the treatments. Therefore, in this study, cover crops were successfully terminated by the roller-crimper, allowing successful strip-till establishment and production of silage maize.